2013
DOI: 10.5812/ircmj.4180
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Knifelight Surgery versus Conventional Open Surgery in the Treatment of Carpal Tunnel Syndrome

Abstract: BackgroundA variety of surgical treatment methods for carpal tunnel syndrome are introduced recently, including open surgery, endoscopic and the Knifelight. It is hypothesized that Knifelight method could decrease scar tenderness and time before return to daily activities for patients and is accompanied with less disturbance to fine sensory nerves.ObjectivesTo compare the Knifelight instrument and open carpal tunnel release with respect to scar length, operation duration, recovery time needed before return to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…On account of the heterogeneity between the groups of interval to return to activities is small ( I 2 = 49%), a fixed effect model is used. Patients who treated with limited carpal tunnel release returned to activities earlier than patients who treated with standard release (MD,−8.80 [−9.21 to −8.39]; P < .01) [18,21,22,24,26,29] (Fig. 4).…”
Section: Main Results Of This Analysismentioning
confidence: 99%
“…On account of the heterogeneity between the groups of interval to return to activities is small ( I 2 = 49%), a fixed effect model is used. Patients who treated with limited carpal tunnel release returned to activities earlier than patients who treated with standard release (MD,−8.80 [−9.21 to −8.39]; P < .01) [18,21,22,24,26,29] (Fig. 4).…”
Section: Main Results Of This Analysismentioning
confidence: 99%
“…Elfar et al stated that conservative therapy generally offers only temporary relief of symptoms 7 ) . On the other hand, some studies have reported that conservative treatment is ineffective, and that almost one-third of patients diagnosed with CTS will require surgery 24 , 25 , 26 ) . Two-thirds of patients who underwent carpal tunnel release reported being completely or very much satisfied with the outcome in follow-up examination 6, 18, and 30 months after surgery 25 ) .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, some studies have reported that conservative treatment is ineffective, and that almost one-third of patients diagnosed with CTS will require surgery 24 , 25 , 26 ) . Two-thirds of patients who underwent carpal tunnel release reported being completely or very much satisfied with the outcome in follow-up examination 6, 18, and 30 months after surgery 25 ) . A number of non-surgical interventions reported in the literature have been useful for the treatment CTS in the short-term, but there is sparse in the evidence of their long-term effectiveness 3 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, endoscopic surgery is advantageous in terms of the time period of pain and before going back to work [8][9][10][11]. However, results were reported regarding the complication rates of these methods [10][11][12][13][14][15][16][17][18][19] (Table 1).…”
Section: Introductionmentioning
confidence: 99%